Open-loop solar tracking strategy for high concentrating photovoltaic systems using variable tracking frequency. (1st June 2016) - Mi, Zhe; Chen, Jikun; Chen, Nuofu; Bai, Yiming; Fu, Rui; Liu, Hu
Highlights: Correlation of solar tracking frequency to photovoltaic system output is quantified. A new tracking strategy has been designed. Varying the solar tracking frequency effectively reduces the mechanical movement. Abstract: High concentrating photovoltaic is one of the most promising photovoltaic techniques that possesses up to now the highest photo to electric conversion efficiency. However, due to the small tolerance in the misfit angle between the incoming solar light and the normal of the solar cell panel, an accurate solar tracking is necessary in order to maintain the high performance. Although increasing the tracking frequency in conventional solar tracking strategy enhances the tracking accuracy, it also increases the moving frequency of the tracking system and the mechanical wear. In order to overcome this limitation, a more efficient solar tracking strategy has been provided by utilizing an open-loop mode to actively control and alter the tracking frequency instead of using constant tracking frequency. The code for controlling of tracking frequency is pre-programmed according to the theoretical solar velocity in different time and date. By correlating the movement from the azimuth and the altitude freedom, the total moving frequency of the solar tracking system has been reduced. As a result, it effectively decreases the moving frequency of the tracking system, which saves the required external energy to drive the tracking system and improves its reliability.